Drug Utilization and Measurement of Medication Adherence: A Real World Study of Psoriasis in Italy - Sara Mucherino; Concetta Rafaniello; Marianna Serino; Alessia Zinzi; Ugo Trama; Annalisa Capuano; Enrica Menditto; Valentina Orlando (MDPI AG, 2023)
Exceptional advances have been made with systemic treatment for psoriasis (PSO). However, that disease still represents a heavy burden in terms of impact on healthcare systems worldwide. This study comprehensively assesses medication adherence in a real world setting in Italy across all phases-initiation, implementation, and persistence-of PSO therapies. By distinguishing between switches and swaps, it provides unique insights into the patient's own approach to prescribed therapy as well as clinical decision-making processes, enhancing our understanding of medication adherence and discontinuation in a real world daily setting. The study's refined methodology for assessing persistence, considering variations in refill gaps and complex dosing regimens, shows that anti-interleukin (IL) therapies are associated with longer periods of adherence compared with other available therapeutic strategies. Among the selected drugs, ixekizumab and secukinumab were the ones with higher rate of treatment adherence at the expense of anti-TNF-α and anti-PDE4 agents. Notably, patients who opt for swaps are approximately 2.8 times more likely to discontinue their PSO therapy within one year. These findings carry practical implications for optimizing medication adherence, including tailored patient counseling, monitoring, and therapeutic adjustments, highlighting the need for a comprehensive and patient-centered approach to managing these conditions.